(untitled) (Research, Society and Development, 2021)
The objective was to analyze the existing dialogue between the CER II/UNESC and the APS through the counter-referral system and the stratification of the epidemiological profile of patients with motor impairment, treated at the CER II/UNESC during the years 2014-2017. Cross-sectional, retrospective and descriptive study, with semi-structured interviews applied through a telephone survey and creation of a database. Sample of 32 patients, 71.9% (n=23) of whom were male, with a mean age of ±55.25 years, 46.9% (n=15) residing in Criciúma, 71.9% (n =19) accepted at CER II/UNESC for post-stroke rehabilitation treatment; time elapsed between the injury and its admission to the service of ±87.31 days, and of stay ±224.91 days. Of the sample, 81.3% (n=26) reported having received a discharge note, 56.3% (n=18) did not use it. 87.5% (n=26) were not sought by the PHC and, of these, 56.3% (n=18) were not referred to the referenced services at the time of discharge. 62.5% (n=20) reported needing some assistance from a specialist physician (12.5%, n=4). A weakened relationship between PHC and CER II/UNESC was observed, with consequent deficient dialogue. Patients find PHC ineffective from an organizational, human and work process perspective. They are not able to reintegrate when they are discharged, having their health needs discovered by the system, so that their potential is not reached, thus worsening their prognosis. It was also observed the fragility of the referral and counter-referral system and the lack of commitment and co-responsibility and the consequent lack of a sense of protagonism on the part of users.